Fortalezas Familiares Y Consumo De Alcohol En Hombres Y Mujeres Adolescentes - Ocampo, Diana Betancourt; González-González, Alejandro; Agüero, María Cristina Pérez (European Scientific Journal, ESJ, 2017)
The present study aimed to analyze the differences in family assets in adolescents, men and women, by level of alcohol consumption. For this, a non-probabilistic sample of 454 high school students was selected, with a mean age of 15.9 years old (SD = 1.07); of which 49.1% were men and 50.9% were women. Three dimensions of the Parental Practice Scale (Andrade & Betancourt, 2008) were used to assess family assets, which assesses the support and supervision of both parents; in addition, the scale house rules of Sánchez-Xicotencatl (2015) was used. To measure alcohol consumption, four indicators were used to evaluate the behavior’s presence, the age of onset, as well as frequency and quantity (Andrade & Betancourt, 2008). The results showed that 57% of men and 53.8% of women reported that they had consumed alcohol. Regarding the differences in family assets by the categories of the alcohol consumption indicator, the findings showed significant differences house rules (in both men and women), and in the men’s case differences were found in maternal supervision and in women, differences were found in the support-supervision of the father. The results allow us to have elements of the role of the assets evaluated in the alcohol consumption in adolescent population, as well as the differential effect by the sex of the adolescents.